The Digitalization Effectiveness as an Innovative Factor Development of the Agriculture in Azerbaijan - Valiyev, Akif; Rustamov, Famil Vali oglu; Huseynova, Ruhiyya Adilqizi; Orujova, Mehpara Sattarqizi; Musayeva, Sevil Nizami (Journal of Eastern European and Central Asian Research (JEECAR), 2022)
The purpose of this paper is to systematize and justify the factors for the effective implementation of digitalization to ensure the innovative development of agriculture in Azerbaijan. Based on the survey completed by 1,513 senior managers of agricultural enterprises in Azerbaijan, the key factors and barriers to digitalization of agriculture were substantiated: the cost of introducing and using digital technologies, unregulated legislative processes of digitalization of the industry, and the level of cybersecurity. The levels of development of digitalization of the country's agricultural sector have been determined and empirically substantiated the qualitative nature of the influence of digitalization factors on the innovative development of agricultural enterprises using the regression modeling method. The results obtained can help develop a state strategy for enhancing the digitalization of the country's agricultural sector to ensure its innovative development, food security, and diversifying the economy.